Revisiting astrocyte to neuron conversion with lineage tracing in vivo - Wang, Lei-Lei; Serrano, Carolina; Zhong, Xiaoling; Ma, Shuaipeng; Zou, Yuhua; Zhang, Chun-Li (Cell, 2021)
In vivo cell fate conversions have emerged as potential regeneration-based therapeutics for injury and disease. Recent studies reported that ectopic expression or knockdown of certain factors can convert resident astrocytes into functional neurons with high efficiency, region specificity, and precise connectivity. However, using stringent lineage tracing in the mouse brain, we show that the presumed astrocyte-converted neurons are actually endogenous neurons. AAV-mediated co-expression of NEUROD1 and a reporter specifically and efficiently induces reporter-labeled neurons. However, these neurons cannot be traced retrospectively to quiescent or reactive astrocytes using lineage-mapping strategies. Instead, through a retrograde labeling approach, our results reveal that endogenous neurons are the source for these viral-reporter-labeled neurons. Similarly, despite efficient knockdown of PTBP1 in vivo, genetically traced resident astrocytes were not converted into neurons. Together, our results highlight the requirement of lineage-tracing strategies, which should be broadly applied to studies of cell fate conversions in vivo.